Bandung City's Parallel Diplomacy in Marketing MSMEs Through the Little Bandung Program in Petaling Jaya - Ramdan, Intan Agatha; Azmi, Fuad (Journal of Law, Politic and Humanities, 2025)
This article discusses the parallel diplomacy practiced by the Bandung City Government through the Little Bandung Program as a marketing strategy for micro, small, and medium enterprises (MSMEs) at the international level. The background of this research stems from the increasing role of subnational actors in international relations and the need for local governments to expand market access for MSMEs as drivers of the local economy. This study aims to analyze how parallel diplomacy is implemented by the Bandung City Government in the Little Bandung program and the role of MSMEs as societal actors supporting subnational diplomacy. This study uses a qualitative approach through the collection of primary data in the form of interviews and secondary data through document studies and relevant literature. The results show that Little Bandung is a practice of parallel diplomacy that is autonomous, based on regional needs, and carried out through cross-actor collaboration, including the city government, MSMEs, foreign partners, and the diaspora community. MSMEs not only play a role as objects of promotion but are also actively involved in cross-cultural interactions and the formation of international economic networks. This study concludes that MSME-based parallel diplomacy can be a strategic instrument for local governments to promote the internationalization of the local economy and enrich the study of subnational diplomacy in International Relations studies.